Faraldsfræði Haemophilus influenzae fyrir og eftir bólusetningu með Prótein D tengdu bóluefni gegn pneumókokkum á Íslandi - Hildigunnur Sveinsdóttir 1985- (2017)
Introduction: Haemophilus influenzae is a Gram-negative coccabacillus that is a frequent colonizer of the respiratory tract of healthy individuals, especially children, and a major cause of infections in humans. H. influenzae can be divided into capsulated and non-capsulated isolates depending on expression of polysaccharide capsule. Encapsulated H. influenzae is classified into six serotypes (a-f), based on antigen expression. Before the introduction of H. influenzae type b vaccination, serotype b (Hib) was the most common cause of life-threatening diseases in children such as, meningitis and epiglottitis. H. influenzae isolates without capsule are defined as non-typeable H. influenzae (NTHi) and are a major cause of respiratory infections including middle ear infections, sinusitis, pneumonia and the most common cause of exacerbation of patients with respiratory diseases. NTHi is rarely causing invasive infection but since the introduction of Hib vaccine, NTHi has become more clinically important. In April 2011, Synflorix was introduced to the childhood vaccination program in Iceland. Synflorix is a 10-valent conjugated pneumococcal vaccine (PhiD-CV, GlaxoSmithKline) where 8 pneumococcal serotypes are conjugated to Protein D (PD) derived from NTHi. PD is encoded by the gene hpd, which is highly conserved among most capsulated and non-capsulated strains of H. influenzae. By using PD as a carrier protein for pneumococcal vaccine serotypes, there is a possibility of providing protection against H. influenzae infections. The epidemiology of H. influenzae and the effect of PD conjugated vaccine are unknown in Iceland. Aims: The aims of this study were to assess effect of the vaccination on the carriage rate of H. influenzae among healthy children in Iceland, the prevalence of the hpd gene and the prevalence of each serotype of H. influenzae both in carriage isolates and in clinical samples. Material and methods: H. influenzae isolates were obtained from nasopharyngeal samples that were collected from healthy ...